Adaptation to coastal flooding and inundation: Mitigations and migration pattern in Semarang City, Indonesia. (1st September 2018) - Buchori, Imam; Pramitasari, Angrenggani; Sugiri, Agung; Maryono, Maryono; Basuki, Yudi; Sejati, Anang Wahyu
Abstract: As a global issue, climate change has been significantly influencing coastal areas and causing changes in marine and terrestrial environments. The increase in sea-level rise (SLR), for example, has worsened the quality of life of coastal communities, and this risk increases especially in coastal cities of the developing world. This paper aims to comprehend the variety of self-mitigations and the patterns of local migrations of communities in the northern part of Semarang City, Indonesia. The delineation of the risk areas for Rob, a local term for inundation and flooding caused by sea water overflow, was accomplished with the application of GIS. Interviews with the inhabitants were conducted to investigate the scale and frequency of Rob and the variety of mitigation, adaptation, and responses at the individual, household or community level. Further investigation was done to comprehend the reasons why people moved away from their current residence to their intended locations. The results show that most inhabitants prefer to stay and to adapt rather than to leave, due to social factors such as being comfortable with their community relationships. Those who wanted to move chose diverse locations spread across various areas of the city. Safer places in the hilly areas of southern Semarang and other residences close to their family or relatives were the most preferable. Based on this understanding, local government should encourage people to be more aware of the potential hydro-meteorological hazards threatening their environment. Highlights: Coastal flooding and inundation in the coastal areas of Semarang City, Indonesia. Mitigations and migration pattern of the Rob-affected communities. Suggestions for local government to empower the City Spatial Plan.